Cyperus esculentus var. sativus Adapts to Multiple Heavy Metal Stresses Through the Assembly of Endophytic Microbial Communities - Qiaofeng Liu; Jialing Lai; Yaozhong Zhang; Xin Wang (Biology)
Interactions between plants and their endophytes alter their metabolic functions and ability to cope with abiotic stresses. In this study, high-throughput sequencing was used to analyze the species diversity and functions of endophytes in Cyperus esculentus var. sativus (CES) tubers under different heavy metal stress conditions. The results indicated that the number of observed endophytic species in the tubers increased under heavy metal stress (p < 0.05), leading to changes in species diversity and composition. The response of tuber endophytes to different metal concentrations varied, with certain endophytic bacteria and fungi, such as Pseudomonas, Novosphingobium, and Fusarium, showing increased abundance and becoming the dominant species in the tubers. Additionally, new endophytic genera, Actinophytocola and Monosporascus, emerged at specific metal concentrations (p < 0.05). Fatty acid salvage was enriched in the endophytes of CES, which may play an important role in assisting CES in responding to multiple heavy metal stresses. These findings showed that CES tuber endophytes undergo adaptive changes to support the ability of plants to cope with heavy metal stress.